Pengaruh Penggunaan Media Aplikasi Perplexity Berbasis AI terhadap Keterampilan Menulis Teks Berita Siswa di Kelas VII SMP : The Effect of Using AI-Based Perplexity Application Media on Students' News Text Writing Skills in Grade VII of Middle School - Eno Nopita Sari Simarmata; Martua Reynhat Sitanggang Gusar; Monalisa Frince S (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the effect of using the Perplexity application media based on artificial intelligence (AI) on the ability to write news texts of seventh-grade students at SMP Negeri 37 Medan. The study population included all seventh-grade students in the 2024/2025 academic year, totaling 255 people, and was divided into eight classes. From this population, a sample of 31 students from class VII-H was taken through a random sampling technique. The research method used was a one-group pretest-posttest design, with the data collection instrument in the form of a news text writing assignment test. The results of the analysis showed that the average pretest score of students before using the Perplexity AI application was 45.16, while the average posttest score after using the application increased to 65.32. The normality test using the Lilliefors method produced an L-count value of 0.120 for the pretest and 0.116 for the posttest, while the L-table at a significance level of 0.05 was 0.159. Thus, both data sets were normally distributed. The homogeneity test shows Fcount = 0.67 and Ftable = 1.84, so the data is declared homogeneous because Fcount <Ftable. Furthermore, the t-test results show tcount of 4.87 with ttable at a significance level of 0.05 of 1.67. Because tcount> ttable (4.87> 1.67), the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Based on these results, the use of the AI-based Perplexity application media has a positive and effective effect in improving the news text writing skills of class VII students of SMP Negeri 37 Medan in the 2024/2025 academic year.